Fsr1, a striatin homologue, forms an endomembrane‐associated complex that regulates virulence in the maize pathogen Fusarium verticillioides. (25th July 2017) - Zhang, Huan; Mukherjee, Mala; Kim, Jung‐Eun; Yu, Wenying; Shim, Won‐Bo
Summary: Fsr1, a homologue of mammalian striatin, containing multiple protein‐binding domains and a coiled‐coil (CC) domain, is critical for Fusarium verticillioides virulence. In mammals, striatin interacts with multiple proteins to form a STRIPAK (striatin‐interacting phosphatase and kinase) complex that regulates a variety of developmental processes and cellular mechanisms. In this study, we identified the homologue of a key mammalian STRIPAK component STRIP1/2 (striatin‐interacting proteins 1 and 2) in F. verticillioides, FvStp1, which interacts with Fsr1 in vivo . Gene deletion analysis indicates that FvStp1 is critical for F. verticillioides stalk rot virulence. In addition, we identified three proteins, designated FvCyp1, FvScp1 and FvSel1, which interact with the Fsr1 CC domain via a yeast two‐hybrid screen. Importantly, FvCyp1, FvScp1 and FvSel1 co‐localize to endomembrane structures, each having a preferred localization in the cell, and they are all required for F. verticillioides stalk rot virulence. Moreover, these proteins are necessary for the correct localization of Fsr1 to the endoplasmic reticulum (ER) and nuclear envelope. Thus, we identified several novel components in the STRIPAK complex that regulates F. verticillioides virulence, and propose that the correct organization and localization of Fsr1 are critical for STRIPAK complex function.